2020
DOI: 10.1111/cmi.13273
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus Hsp90 interacts with the main components of the cell wall integrity pathway and cooperates in heat shock and cell wall stress adaptation

Abstract: The initiation of Aspergillus fumigatus infection occurs via dormant conidia deposition into the airways. Therefore, conidial germination and subsequent hyphal extension and growth occur in a sustained heat shock (HS) environment promoted by the host. The cell wall integrity pathway (CWIP) and the essential eukaryotic chaperone Hsp90 are critical for fungi to survive HS. Although A. fumigatus is a thermophilic fungus, the mechanisms underpinning the HS response are not thoroughly described and important to def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 94 publications
6
29
0
Order By: Relevance
“…However, it remained unclear how hsfA HSF 1 contributes to thermal adaptation and the disturbed cell wall homeostasis observed in the CWI pathway mutants. This is a follow-up study to our previous work (Rocha et al, 2020b), and our results show that cell wall ultrastructure is severely modified when cells are exposed to HS. We observe that hsfA is essential for thermotolerance, impacts the expression of genes related to the cell wall biosynthesis, and genetically interacts with the main players of the CWI and HOG pathway.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, it remained unclear how hsfA HSF 1 contributes to thermal adaptation and the disturbed cell wall homeostasis observed in the CWI pathway mutants. This is a follow-up study to our previous work (Rocha et al, 2020b), and our results show that cell wall ultrastructure is severely modified when cells are exposed to HS. We observe that hsfA is essential for thermotolerance, impacts the expression of genes related to the cell wall biosynthesis, and genetically interacts with the main players of the CWI and HOG pathway.…”
Section: Introductionsupporting
confidence: 77%
“…Also, Hsp90 potentiates the resistance to echinocandins in different fungal pathogens, including A. fumigatus, since depletion of this chaperone increases the susceptibility to these antifungals (Cowen, 2009;LaFayette et al, 2010;Lamoth et al, 2013Lamoth et al, , 2015Chatterjee and Tatu, 2017). We have previously demonstrated that three critical components of the A. fumigatus CWI pathway (PkcA, MpkA, and RlmA) are Hsp90 clients (Rocha et al, 2020b), suggesting an involvement of the Hsf1-Hsp90 regulatory function over the A. fumigatus CWI pathway. However, it remained unclear how hsfA HSF 1 contributes to thermal adaptation and the disturbed cell wall homeostasis observed in the CWI pathway mutants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PkcA is a critical kinase in the CWI pathway and necessary for fungal survival during exposure to antifungal drugs [78]. In the current study, mutations in the C1B domain of PkcA prevented interaction with Hsp90, abolishing the CWI pathway response and supporting the potential of PkcA as a novel antifungal target; however, similarity with the host PKCβII protein demonstrates cross-reactivity and blocking [77]. These findings determined that CWI proteins are Hsp90 substrates, and Hsp90 stabilizes the CWI proteins, regulating response to heat stress.…”
Section: Ptms Influence Antifungal Resistancesupporting
confidence: 50%
“…For example, in C. albicans, Hsp90 is phosphorylated by regulatory subunits of kinase CK2, impacting the stability and function of Hsp90 targets, including Hog1, which is necessary for stress response [75] (Figure 4B). Another example encompasses the role of CWI components (e.g., PkcA, MpkA, and RlmA), which interact with Hsp90 during heat shock and cell wall stress adaptation [77]. PkcA is a critical kinase in the CWI pathway and necessary for fungal survival during exposure to antifungal drugs [78].…”
Section: Ptms Influence Antifungal Resistancementioning
confidence: 99%